Dual Functional Alginate‐Polyethylene Polyamine Composite Aerogel Toward Sensing and Extracting Copper Ions in Water. Issue 7 (15th February 2021) - Wang, Zhuqing; Yang, Leilei; Yang, Qi; Wang, Min
Abstract: In this study, a new type of sodium alginate‐polyethylene polyamine composite aerogel (Alg‐PEMA) was synthesized to detect and remove excess copper ions (Cu 2+ ) in water. First, a classic acylation reaction was used to graft polyethylene polyamine onto alginate, which was then gelatinized in a calcium ion solution and vacuum freeze‐dried to prepare the final Alg‐PEMA adsorbent. Experimental results showed that the as‐prepared Alg‐PEMA can remove 99.2 % of Cu 2+ (0.1 mM) in water, and the maximum adsorption capacity for Cu 2+ is 46.78 mg/g. Alg‐PEMA can also be used for qualitative colorimetric detection of Cu 2+ in aqueous solution. The detection limit for Cu 2+ is as low as 0.64 mg/L, which is lower than the WHO standard for drinking water Cu 2+ content (2.0 mg/L). Its green and safe raw materials, simple desorption and regeneration process, and stable detection and adsorption performance indicate that the Alg‐PEMA adsorbent has broad application prospects in the treatment of Cu 2+ ‐containing wastewater. Abstract : A novel dual‐functional sodium alginate‐polyethylene polyamine composite aerogel (Alg‐PEMA) was synthesized to detect and remove excess copper ions (Cu 2+ ) in water. The as‐prepared Alg‐PEMA can remove more than 99.0 % of Cu 2+ from a single or mixed ions solution, and the detection limit of Alg‐PEMA for Cu 2+ is as low as 0.64 mg/L. It can be used as a sensor to qualitatively colorimetric detect of Cu 2+ in water.